2020
DOI: 10.1155/2020/9082179
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Mortality in Dodoma Regional Referral Hospital, Tanzania

Abstract: Background. Maternal mortality has remained a challenge in Tanzania. The Tanzania Demographic and Health Survey 2015-16 has shown that the problem has been increasing despite various strategies instituted to curb it. It has been shown that most of the maternal deaths occurring in health facilities, whether direct or indirect, have other contributing factors. The objective of this study was to analyse causes and associated factors for maternal deaths in Dodoma Regional Referral Hospital (DRRH). Methods. A retro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 16 publications
1
22
0
Order By: Relevance
“…Accurate classification of causes of maternal mortality is vital for decision making and provision of care; otherwise there could be misclassification and under-identification of maternal deaths at facilities, where a woman of reproductive age may die in a medical or surgical ward with an undiagnosed obstetric complication ( 25 ). For programmatic purposes, indirect causes of maternal mortality require greater attention, not just for purposes of reporting, but also for timely decision making and interventions to prevent these deaths ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accurate classification of causes of maternal mortality is vital for decision making and provision of care; otherwise there could be misclassification and under-identification of maternal deaths at facilities, where a woman of reproductive age may die in a medical or surgical ward with an undiagnosed obstetric complication ( 25 ). For programmatic purposes, indirect causes of maternal mortality require greater attention, not just for purposes of reporting, but also for timely decision making and interventions to prevent these deaths ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…The sample size was calculated using the formula for quantitative studies ( n = Z 2 P (1 − P )/ d 2 ) 18 with the following assumptions: n is the required sample size, P is the proportion (33.5%) of knowledge and hygienic practices for postpartum women, 11 d is the margin of error to the desired level of precision to the true value (5%), and Z is the constant standard normal variation (1.96 for 95% confidence level). Proportionate sampling method was adapted to handpick the number of study participants from each selected facility using the following formula: n i = N i / N t * n , whereas n i is the required number of respondents per each facility, N i is the total number of deliveries per each facility per day, N t is the total number of deliveries in all selected facilities, and n is the total sample size.…”
Section: Methodsmentioning
confidence: 99%
“… 10 Another study which was conducted in Dodoma region indicated that among 35 maternal deaths, 12 were due to puerperal sepsis. 11 …”
Section: Introductionmentioning
confidence: 99%
“…By 2015, the maternal mortality rate in Tanzania was estimated to be 556 maternal deaths per 100,000 live births [ 7 ]. Among the factors contributing to Tanzania’s high maternal mortality rate is a weak referral system [ 8 ]. An efficient and effective referral system is critical to respond to complications which necessitate the transfer a woman and/or new-born with intrapartum complications to the next level health facility.…”
Section: Introductionmentioning
confidence: 99%